2007
DOI: 10.1074/jbc.m703951200
|View full text |Cite
|
Sign up to set email alerts
|

S100B and S100A6 Differentially Modulate Cell Survival by Interacting with Distinct RAGE (Receptor for Advanced Glycation End Products) Immunoglobulin Domains

Abstract: S100 proteins are EF-hand calcium-binding proteins with various intracellular functions including cell proliferation, differentiation, migration, and apoptosis. Some S100 proteins are also secreted and exert extracellular paracrine and autocrine functions. Experimental results suggest that the receptor for advanced glycation end products (RAGE) plays important roles in mediating S100 protein-induced cellular signaling. Here we compared the interaction of two S100 proteins, S100B and S100A6, with RAGE by in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
221
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(230 citation statements)
references
References 65 publications
8
221
1
Order By: Relevance
“…Low concentrations of ROS may even mimic the action of growth factors [44]. Interestingly, the increase in intracellular ROS levels by extracellular psoriasin was in the same range as that previously demonstrated for S100B [45].…”
Section: Discussionsupporting
confidence: 78%
“…Low concentrations of ROS may even mimic the action of growth factors [44]. Interestingly, the increase in intracellular ROS levels by extracellular psoriasin was in the same range as that previously demonstrated for S100B [45].…”
Section: Discussionsupporting
confidence: 78%
“…These include advanced glycation end products ( Schmidt et al, 1992), the chromatin-binding protein HMGB1 (Huttunen et al, 2000;Tian et al, 2007), as well as several members of the S100 family (Hofmann et al, 1999;Leclerc et al, 2007) leading to either a trophic or a toxic cellular effect. We recently showed that S100B and S100A6, two structurally closely related RAGE ligands, interact with distinct domains of the receptor and activate distinct signaling pathways suggesting that the cellular effects triggered by RAGE might be specific for each ligand .…”
Section: Rage Is Implicated In A␤o-mentioning
confidence: 99%
“…RAGE ligands include S100/calgranulins (S100A4, S100A6, S100A7, S100A8/9, S100A14, S100B and S100P) (2,(25)(26)(27)(28)(29) and HMGB-1 protein, which have been demonstrated to be upregulated in glioma, melanoma, bladder, liver, pancreatic, prostate, colorectal, gastric and lung cancer (30)(31)(32)(33)(34). Ligand-RAGE signaling pathways enhance the properties associated with malignant tumor phenotypes (10,22,(35)(36)(37), including by activating members of the small GTPase family (Cdc42 and Rac1), members of the mitogen-activated protein kinase family (extracellular signal-regulated kinase, p38 and stress-activated protein kinases/c-Jun amino-terminal kinases), NF-κB and the formin homology 1 domain (10,22,35-37).…”
Section: Discussionmentioning
confidence: 99%